Geometridae Stephens, 1829 from different altitudes in Western Himalayan Protected Areas of Uttarakhand, India (Lepidoptera: Geometridae) - A. K. Sanyal; P. Dey; V. P. Uniyal; K. Chandra; A. Raha (SHILAP)
The Geometridae Stephens, 1829 are considered as an excellent model group to study insect diversity patterns across elevational gradients globally. This paper documents 168 species of Geometridae belonging to 99 genera and 5 subfamilies from different Protected Areas in a Western Himalayan state, Uttarakhand in India. The list includes 36 species reported for the first time from Uttarakhand, which hitherto was poorly explored and reveals significant altitudinal range expansion for at least 15 species. We sampled different vegetation zones across an elevation gradient stretching from 600 m up to 3600 m, in Dehradun-Rajaji landscape, Nanda Devi National Park, Valley of Flowers National Park, Govind Wildlife Sanctuary, Gangotri National Park and Askot Wildlife Sanctuary. The subfamily Ennominae represented the maximum number of species, and the species of subfamily Larentiinae were found to be more restricted to higher elevation areas. Western Mixed Coniferous forest held the greatest number of species, whereas the Subalpine forest was characterized by the highest number of indicator species identified through Indicator Species Analysis. While Indo-Malayan species dominated the assemblage composition, the maximum number of Himalayan endemics suggested that these species are long adapted to the Himalayan climatic gradient and ongoing climate-mediated perturbation may hamper their future survival.